Reconciliation of the excess 176Hf conundrum in meteorites: Recent disturbances of the Lu-Hf and Sm-Nd isotope systematics. (1st September 2017) - Bast, Rebecca; Scherer, Erik E.; Sprung, Peter; Mezger, Klaus; Fischer-Gödde, Mario; Taetz, Stephan; Böhnke, Mischa; Schmid-Beurmann, Hinrich; Münker, Carsten; Kleine, Thorsten; Srinivasan, Gopalan
Abstract: The long-lived 176 Lu- 176 Hf and 147 Sm- 143 Nd radioisotope systems are commonly used chronometers, but when applied to meteorites, they can reveal disturbances. Specifically, Lu-Hf isochrons commonly yield dates up to ∼300 Myr older than the solar system and varying initial 176 Hf/ 177 Hf values. We investigated this problem by attempting to construct mineral and whole rock isochrons for eucrites and angrites. Meteorites from different parent bodies exhibit similar disturbance features suggesting that a common process is responsible. Minerals scatter away from isochron regressions for both meteorite classes, with low-Hf phases such as plagioclase and olivine typically being most displaced above (or left of) reference isochrons. Relatively Hf-rich pyroxene is less disturbed but still to the point of steepening Lu-Hf errorchrons. Using our Lu-Hf and Sm-Nd data, we tested various Hf and Lu redistribution scenarios and found that decoupling of Lu/Hf from 176 Hf/ 177 Hf must postdate the accumulation of significant radiogenic 176 Hf. Therefore early irradiation or diffusion cannot explain the excess 176 Hf. Instead, disturbed meteorite isochrons are more likely caused by terrestrial weathering, contamination, or common laboratory procedures. The partial dissolution of phosphate minerals may predominantly remove rare earth elements including Lu, leaving relatively immobile and radiogenic Hf behind. Robust Lu-Hf (and improved Sm-Nd) meteorite geochronology will require the development of chemical or physical methods for removing unsupported radiogenic Hf and silicate-hosted terrestrial contaminants without disturbing parent-daughter ratios.